Perlindungan Hukum Kreditor Dalam Warisan Atas Harta Peninggalan Tak Terurus Menurut Sistem Waris Barat - Rifaldi Setiawan, Muhammad; Fakhry, Muhammad; Apriano, Mahardika (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The enactment of inheritance law in Indonesia adheres to 3 (three) inheritance law systems, namely; First, Western Inheritance Law, Second, Customary Inheritance Law, Third, Islamic Inheritance Law. So that in Indonesia is known for the pluralism of inheritance law. The western inheritance legal system allows for heirs to reject the inheritance left by the heirs because there is a greater pasiva than the assets. then the status of the property will be an unmanageable inheritance. Doctrinal research method, which is a study that systematically examines the legal norms governing certain legal categories and analyzes the relationship between legal norms. In this case the state through the Heritage Hall that will manage the property. As a form of protection creditors can apply to be a replacement heir for the deposit of receivables will be carried out by the state through the Heritage Hall a number with the value of the heir's debt or or the value of the property or objects left by the heirs is sufficient.